1997
DOI: 10.1007/s002239900225
|View full text |Cite
|
Sign up to set email alerts
|

High Bone Turnover is Associated with Low Bone Mass and Spinal Fracture in Postmenopausal Women

Abstract: A group of 366 healthy, white postmenopausal women, aged 50-81 years, mean age 66 years, were selected from the screened population of Scandinavians who were part of a multicenter study of the efficacy of tiludronate, a new bisphosphonate, in established postmenopausal osteoporosis. Eighty-eight women had a lumbar spine bone mineral density (BMD) above 0.860 g/cm2, and 278 women had a BMD below 0.860 g/cm2. Spinal fracture was diagnosed from lateral spine X-ray studies and defined as at least 20% height reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
34
0
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 17 publications
9
34
0
3
Order By: Relevance
“…These markers have been extensively used for both the assessment of therapeutic efficacy of antiresorptive drugs in osteoporosis and for prediction of fracture risk in postmenopausal women [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. We measured urinary and serum CTx and urinary NTx in a large cohort of untreated, healthy women stratified on the basis of their menopausal status and BMD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These markers have been extensively used for both the assessment of therapeutic efficacy of antiresorptive drugs in osteoporosis and for prediction of fracture risk in postmenopausal women [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. We measured urinary and serum CTx and urinary NTx in a large cohort of untreated, healthy women stratified on the basis of their menopausal status and BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, biochemical markers of bone turnover provide a rapid assessment of the effects of antiresorptive therapies such as hormone replacement therapy, bisphosphonates, and calcitonin which induce a decrease in the levels of bone markers that is correlated with the long-term effect of such treatments on bone mass [5][6][7][8][9][10][11][12][13][14][15]. Due to the small annual changes in BMD, the effect of antiresorptive therapy can only be reliably monitored by BMD measurement after several years followup [5,10,13].Bone markers might also be used to prognose a high rate of bone less in postmenopausal women who would subsequently develop osteoporosis and fractures [16][17][18][19][20][21][22][23][24][25]. Bone turnover increases after menopause and remains elevated in late postmenopausal women.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ravn et al (1996) observed 979 women and found that high bone turnover is associated with a significantly lower bone mass in menopausal women. Then they further indicated that high bone turnover is a risk factor for osteoporosis (Ravn et al, 1997). Harkness et al (2004) found that soy isoflavones significantly decreased bone resorption and significantly increased bone mineral density within 24 weeks.…”
Section: Effects Of Isoflavone On Bone Resorption and Formation D-f Mmentioning
confidence: 99%